Effects of Pregnancy on Serum Calcium, Magnesium and Inorganic Phosphate Ions in Relation to Osteo-Diseases - Rashid, Shah Samiur; Ishmael, Ukaegbu Chinonso; Chibuike, Ukaegbu Benjamin; Basheer, Esmail Abdullah Mohammed (ISSR, 2014)
Many women suffer from one form of bone related disease or the other at one time or the order during their lives after child bearing age. Research suggested that this problem could be related to the activities going on within the body of the women during their pregnancy days and little or no effort have been made to find out the cause of this problem and offer solution to it. Cases of osteoporosis, osteomalacia, arthritis and its related problems have been a common case among the women. This work was designed to find out the serum calcium, magnesium and inorganic phosphate levels in pregnancy, monitor the changes that occur on these minerals as pregnancy progresses. Serum concentration of Calcium, magnesium and inorganic phosphate were estimated in pregnancy, involving 30 pregnant women (10 for each trimester),and 30 non pregnant women as controls, age ranging between 25-45years. Significant levels of changes (decreased)were noted statistically at 5% level of significance. The mean ±standard deviation value of calcium, magnesium and inorganic phosphate of the test group was 2.27±0.31mmol/L, 0.87±0.15mmol/l and 0.76±0.46mmol/l respectively, were compared to 2.53±0.25 mmol/l 0.93±0.09mmol/l and 1.06±0.42mmol/l for the controls respectively, significantly differences at 5% level of significance were recorded. At different trimesters, there was a corresponding decrease with increase in gestation age, though inorganic phosphate recorded no statistical significant change at first trimester. Its concluded that low levels of these minerals before pregnancy could result to level depletion even before pregnancy concludes and subsequently leads to some of the diseases faced by women after pregnancy.